Social biology of Liostenogaster leonardin. sp. (Hymenoptera, Vespidae, Stenogastrinae) - Abu Bakar, N.A.; Turillazzi, F.; Abdullah, Nurul Ashikin; Hashim, Rosli; Turillazzi, S. (Taylor & Francis, 2016)
The biological, social behavior, immature brood, and nest architecture characteristics of the new species, Liostenogaster leonardi S. Turillazzi & F. Turillazzi n. sp., have been studied in a population of colonies in a gazebo of a mountain locality of Peninsular Malaysia. This species shares the main biological features of other species belonging to the genus Liostenogaster and builds nests exclusively using mud material. Its colonies are composed of a limited number of individuals but in some cases, a large number of males can be found on the same nests. More than one fertilized female is present in the same colony.